PENGARUH NILAI PASAR, PROFITABILITAS, ECONOMIC VALUE ADDED, DAN INFLASI TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - ABDI ZAKARIA, ACHMAD (Jurnal Ilmu Manajemen (JIM), 2017)
This research aims to test the influence of market value, profitability, economic value added and inflation on the Stock Return. Type of this research is quantitative research in the form of causality. The population of this research totalled 69 companies, with as many as 47 companies research samples are taken using a purposive sampling.This research method using multiple linear regression. The object of this research is the financial sector companies were listed on the Indonesia stock exchange period 2013-2015. The data used are secondary data obtained from the official website of the Indonesia stock exchange.The results of this research show that partially variable market values and economic value added has no effect on stock return. While the profitability and inflation influential positive on stock return. The variable of market value has no effect on stock return cause EPS is the accrual profit and easily manipulated. Economic value added has no effect on stock return cause EVA is not a value that dominates the income investors in return. Variable profitability influential positive on stock return cause ROA give a signal to the investors to be able to estimate return. Variables inflation influential significant positive on stock return company cause of the mild and reasonable inflation will encourage the investment climate. Simultaneously, the variable market value, profitability, economic value added and inflation has significant effect on stock return company. Keywords: Market Value, Profitability, Economic Value Added, Inflation, Stock Return.